Exploration of Digital Marketing Strategy for New Market Acquisition in The Family Company PT. Agro Komoditi Lestari - Dandy Bhagaswara (Journal Research of Social Science, Economics, and Management, 2021)
Technology is a breakthrough in the modern era, allowing humans to access information, interact without meeting face to face and in direct contact. This change in human behavior has a direct impact on almost all aspects of life, one of which is the world of economics and business, which in the end the term Digital Marketing was born. This research is qualitative and uses a semi-structured interview method as well as a documentation study in data collection and data analysis. The findings in this study result that the strategy that can be used for the company PT. Agro Komoditi Lestari is implementing digital marketing, internal and external analysis is required, the internal analysis includes the fields of company, product, human resources or financial capabilities, and infrastructure, the external analysis includes segmentation, targeting, and positioning, to determine what platform the company will use, and how to design it. implemented strategy. The use of platforms such as websites, SEO, and SEM is one of the alternative options that can be used by companies that have a B2B market. Social media can also play a good role in a long-term strategy, namely to build brand awareness and foundation capital for the company when it will enter into a more general market or B2C.